Edukasi Gizi sebagai Upaya Pencegahan Balita Stunting di Tanjung Jabung Barat - Arnati Wulansari (Jurnal Abdimas Kesehatan (JAK), 2022)
The problem of stunting is one of the nutritional problems in the world, especially in poor and developing countries. Stunting is a problem because it is associated with an increased risk of illness and death, suboptimal brain development, resulting in delayed motor development and stunted mental growth. For this reason, stunting needs to be prevented from an early age. On of the prevention efforts is training and counseling cadres related to stunting. Cadres are agents of community mobilization who assist in the proper implementation of the posyandu. For this reason, the cadres understanding of stunting must be improved. This community service activity is carried out at the community Health Centre Tungkal II, Tanjung Jabung Barat Regency. This activity will be held in Desember 2019. The target of this activity is cadres. The methode used in the implementation of this activity is the lecture and demonstration method. The results obtained in this activity are the goal of understanding material about stunting and also being able to demonstrate anthropometric measurements (weight and length/height). It is recommended that the community Health Centre Tungkal II be able ti work training related to stunting education so that cadres can understand the importance of preventing and overcoming stunting.